The Influence of Sustainable Consumption Attitudes and Information Anxiety on The Behavior of Buying Organic Products With Consumer Assessment as a Mediator (In The Context of The Covid-19 Pandemic in Surabaya) - Lakshita Dwita Purwasono (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study aims to determine the influence of sustainable consumption attitudes and information anxiety on consumer assessment and its impact on the behavior of buying organic products in the city of Surabaya. The variables used in this study are sustainable consumption attitudes and information anxiety as a free variable, consumer judgment as a mediating variable and organic product buying behavior as bound variables. The method used is quantitative mediation. The samples used in this study used a non-probability sampling method with a combination technique of purposive sampling and snowball sampling. Data collection techniques in this study were carried out by distributing questionnaires using a Likert scale with 107 respondents of Surabaya residents as the population and residents of Surabaya who have purchased organic products during the Covid-19 pandemic. The results of this study indicate that the attitude toward sustainable consumption has a significant influence on consumer ratings, information anxiety has a significant influence on consumer judgment, consumer judgment has a significant influence on buying behavior, information anxiety has no influence on buying behavior with consumer valuation on organic products as a mediator variable, and sustainable consumption attitudes have an influence on buying behavior with consumer judgment as the mediator variable.